Propagation of Polarized Cosmic Maser Radiation in an Anisotropic Magnetized Plasma - Moskaliuk, S.S. (Український фізичний журнал, 2010)
The polarization plane of the cosmic maser radiation (CMR) can be rotated either in the space-time with a metric of the anisotropic Bianchi-I type or in a magnetized plasma. A unified treatment of these two phenomena is presented for cold anisotropic plasma. It is argued that the generalized expressions derived in the present study may be relevant for direct searches of a possible rotation of the plane of polarization of the cosmic maser radiation. Площина поляризацiї випромiнювання космiчного мазера може обертатися як у просторi з анiзотропною метрикою типу Б’янки-I, так i в анiзотропнiй замагнiченiй плазмi. У випадку холодної плазми цi явища описуються в межах єдиного пiдходу. Показано, що отриманi в даному дослiдженнi узагальненi вирази можуть стати у нагодi при безпосереднiх вимiрюваннях величини обертання площини поляризацiї випромiнювання космiчного мазера.